Soybean growth and yield planted at different planting densities - Jaffri, Mohd Nabil (2015)
Soybean (Glycine max) planted at different planting density may affect growth and grain yield. Thus, a study was held to evaluate planting density on crop grain yield and to determine the best planting density which contributes the highest grain yield. In this study, Willis soybean variety was planted at 3 planting densities which were at 15, 30 and 50 plant m-1 in RCBD experimental design. Sampling of fresh weight, dry weight and height of plants were done 2 week after the day of planting and repeated weekly from R1 (flowering stage) to R7 stage (physiological maturity stage). Plants were harvested to determine yield components at R8 (maturity growth stage). The results showed that planting density 15 plants m-1 give out the highest growth performance (fresh weight, dry weight, and height) but planting 30 plants m-1 give out highest grains yield. Although planting 30 plants m-1 showed the highest grains yield, the data showed no significant difference compared with other planting densities. Thus, planting soy bean crops at planting densities of 15, 30 and 50 plant m-1 will have no effect on grain yield and yield components.